Fundamental frequency variation within neonatal crying: Does ambient language matter?. (1st October 2016) - Wermke, Kathleen; Teiser, Johanna; Yovsi, Eunice; Kohlenberg, Paul Joscha; Wermke, Peter; Robb, Michael; Keller, Heidi; Lamm, Bettina
Abstract : Objective : Evaluate the fundamental frequency (fo) variabilty of spontaneous cries produced by neonates with tonal (Lamnso) and non-tonal (German) ambient language. Study Design : Populational prospective study. Participants : A total of 21 German infants (10 male) and 21 Cameroon (Nso) infants (10 male) within the first week of life served as participants. Methods : Spontaneously uttered cries by each infant were audio recorded. The cries were acoustically analyzed and measures of fo variability (pitch sigma, fo fluctuation, fo range) were calculated. Cry duration and anthropometric measures were calculated as co-factors. Results : Significant group differences were found for all fo variability measures, whereas somatic measures did not differ. Cry duration also differed significantly between groups. The results were indicative of Cameroon (Nso) infants producing cries with more fo variability compared to German infants. Conclusion : Albeit further studies with a larger sample size are warranted, the data foster previous findings of an early imprinting effect of the ambient maternal language on cry fo.